Effectiveness and safety of transarterial chemoembolization combined with PD-1 inhibitors and lenvatinib for unresectable intrahepatic cholangiocarcinoma - Jin-Tao Huang; Di Hu; Xin Hong; Wen-Jie Zhou; Jian Shen; Peng-Hua Lv; Xiao-Li Zhu (European Radiology Experimental, 2025)
Abstract Background The objective of this study was to evaluate the therapeutic effectiveness and safety of transarterial chemoembolization (TACE) combined with programmed cell death-1 (PD-1) inhibitors and lenvatinib in the treatment of unresectable intrahepatic cholangiocarcinoma (uICC). Methods This multicenter retrospective study screened patients with uICC who underwent TACE in combination with PD-1 inhibitors and lenvatinib between January 2019 and June 2023. Tislelizumab or camrelizumab (200 mg) was intravenously administered every three weeks. The daily dose of lenvatinib was 8 mg for patients weighing < 60 kg and 12 mg for those weighing ≥ 60 kg. In cases of disease progression, the therapeutic strategy was adjusted based on the clinical condition and individual patient’s treatment preferences. Options included transitioning to standard or supportive care or continuing treatment with TACE in combination with PD-1 inhibitors and lenvatinib. The primary outcomes were overall survival (OS) and progression-free survival (PFS), while secondary outcomes included the objective response rate (ORR), disease control rate (DCR), and the incidence of adverse events (AEs). Results A total of 59 patients with uICC were included. Over a median follow-up period of 32.3 months, the median OS and PFS were 25.8 months (95% confidence interval [CI]: 17.9–33.7) and 9.5 months (95% CI: 7.9–11.0), respectively. The ORR was 55.9%, and the DCR was 96.6%. Grade 3 or four AEs were observed in 15 of 59 patients (25.4%). Conclusion TACE combined with PD-1 inhibitors and lenvatinib demonstrated a promising therapeutic potential with a manageable safety profile for patients with uICC. Relevance statement The combination of TACE, PD-1 inhibitors, and lenvatinib represents a novel therapeutic option for patients with uICC. Key Points TACE plus PD-1 inhibitors and lenvatinib represent a promising therapeutic strategy for uICC. The safety profile of TACE plus PD-1 inhibitors and lenvatinib was manageable. This study demonstrated improved outcomes compared to prior standard-of-care treatments. Graphical Abstract